Employees’ metacognitive knowledge and skills assessment in tourism and hospitality - Valachis, Ioannis; Tachmatzidis, Dimitrios (Journal of Tourism Management Research, 2023)
This research explores academic knowledge, cognitive, emotional, and soft skills, according to the employees’ perceptions, that lead to better service provision and career development enhancement in the tourism and hospitality industry. Moreover, the research explores the possible differences and correlations in reference to five individual traits: the educational background, the tourism and hospitality sectors, the seasonal or full-time character of the organization, the location of the organization, and the working experience derived. In order to investigate the perceptions of employees, 102 online questionnaires were fully completed. Cronbach’s Alpha index, descriptive statistical analysis, correlations between first-ordinal factors, and several MANOVA tests provide information regarding the metacognitive assessment of the above-mentioned domains. According to their responses, the most important academic knowledge that entails the international nature of the Tourism and Hospitality Industry, is ‘International Hospitality Management’. English is the most important foreign language, and Tourism Business Management is the most essential academic knowledge. The most important skills for the Tourism and Hospitality Industry that arise from the research are those of ‘problem solving’, ‘dealing with clients’, ‘customer service’, ‘crisis management’, ‘self-control, and ‘empathy’. The research concluded that, according to employees’ responses, skills and knowledge in the tourism and hospitality industry are generic and universal in their nature and applicability, and they do not differ regarding their individual characteristics. The analysis of the research data provides fruitful information regarding the most important and essential skills and knowledge for the tourism and hospitality industry.